20‐3: Ultra‐High‐Performance Blue Fluorescent OLED with Efficiency Over 250 cd/A/CIEy Using Organic Carrier‐Transport Material with Low Refractive Index. Issue 1 (28th June 2021) - Watabe, Takeyoshi; Kawano, Yuta; Kubota, Tomohiro; Tomida, Airi; Kitano, Yasushi; Tosu, Takao; Fukuda, Keito; Narukawa, Ryo; Nowatari, Hiromi; Ohsawa, Nobuharu; Seo, Satoshi; Yamazaki, Shunpei
Abstract : By developing low‐refractive‐index organic hole‐ and electron‐transport materials enabling the efficiency (cd/A/CIEy) of a top‐emission blue fluorescent OLED to be increased by 12% and 11%, respectively, the blue fluorescent OLED has achieved the ultra‐high efficiency over 250 ca/A/CIEy without the need of a special light‐outcoupling structure or film.